New directions in counselling - Bayne, Rowan; Horton, Ian, 1940-; Bimrose, Jenny, 1949- (Routledge, 1996)
Responds to the major changes affecting counselling - national and European legislation, drive for greater professionalism, accountability, competency and multiculturalism. Considers implications of accreditation and NVQs.